Determining the University's Goals: the Setting of the Problem - Campbell, Duncan D. (Canadian Journal of Higher Education, 1975)
The Canadian university has moved from a decade of rapid expansion, accompanied by general public approval, to the so-called "steady state," of the 1970's, characterized by sharp public questioning of its directions and of its relevance. Criticism from both public and academics alike centres on the lack of consensus within the institution as to its purposes. Certain major factors have the potential to influence a university's choice of goals. Some of these flow out of the network of relationships of the university with its external environment while others stem from the social world of the institution itself. The paper concludes that, given expressions of public concern and what appear to be basic shifts in the fabric of Canadian society — and thus of its requirements of higher education - the re-consideration of institutional goals has become vital.